A thermo-mechanical interface model for simulating the bond behaviour of FRP strips glued to concrete substrates exposed to elevated temperature - Caggiano, Antonio (2015)
This paper proposes a model aimed at simulating the bond behaviour of Fiber Reinforced Polymer (FRP) laminates glued to concrete substrates and exposed to high temperature. Based on a previous model already formulated by one of the authors and available in the scientific literature, the present paper proposes a theoretical model formulated within the general framework of Fracture Mechanics and Plasticity-based concepts. Particularly, the aforementioned model is extended herein to consider the thermal effects, through a temperature-based scaling function affecting the strength parameters and softening rules which define the failure surface and the post-cracking response of FRP-concrete joints. The mechanical soundness of the proposed model is demonstrated by the very good agreement between some experimental results taken from the scientific literature on FRP-to-concrete systems tested in pull-out loading at normal and elevated temperature and the corresponding theoretical simulations.